∫ 0 4 x 2 + 9 − x x 2 + 9 ( x + x 2 + 9 ) d x
Find the value of the closed form of the above integral to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
wow! this is the shortest substitution so far!!
First we set Euler substitution x 2 + 9 = x + t . This leads to:
x 2 + 9 = x 2 + 2 x t + t 2
x = 2 t 9 − t 2
d x = − 2 t 2 9 + t 2 d t
x 2 + 9 = 4 t 2 8 1 − 1 8 t 2 + t 4 + 9 = 2 t 9 + t 2
So:
∫ 0 4 x 2 + 9 − x x 2 + 9 ( x + x 2 + 9 ) d x
Becomes:
∫ 3 1 2 t 9 + t 2 − 2 t 9 − t 2 2 t 9 + t 2 ( 2 t 9 − t 2 + 2 t 9 + t 2 ) ⋅ − 2 t 2 9 + t 2 d t
= ∫ 1 3 t 2 t 9 + t 2 ⋅ 2 t 1 8 ⋅ 2 t 2 9 + t 2 d t
= 4 9 ∫ 1 3 t 5 ( 9 + t 2 ) 2 d t
= 4 9 ∫ 1 3 ( t 1 − t 3 1 8 + t 5 8 1 ) d t
= 4 9 ( l n ( t ) ∣ ∣ ∣ 1 3 − t 2 9 ∣ ∣ ∣ 1 3 − 4 t 4 8 1 ∣ ∣ ∣ 1 3 )
= 4 9 ( l n ( 3 ) − ( 1 − 9 ) − ( 4 1 − 4 8 1 ) )
= 4 9 ( l n ( 3 ) + 2 8 )
= 6 3 + 4 9 l n ( 3 )
≈ 6 5 . 4 7 2
Brilliant method! I went through an ordeal when I tried to rationalize the denominator and then used trigonometric substitution.
x=3tanv could also be helpuful substitution
I = ∫ 0 4 x 2 + 9 − x x 2 + 9 ( x + x 2 + 9 ) d x = ∫ 0 4 ( x 2 + 9 − x ) ( x 2 + 9 + x ) x 2 + 9 ( x + x 2 + 9 ) 2 d x = 9 1 ∫ 0 4 x 2 + 9 ( x + x 2 + 9 ) 2 d x Let x = 3 tan θ , d x = 3 sec 2 θ d θ = 9 1 ∫ 0 tan − 1 3 4 3 sec θ ( 3 tan θ + 3 sec θ ) 2 ⋅ 3 sec 2 θ d θ = 9 ∫ 0 tan − 1 3 4 sec 3 θ ( tan θ + sec θ ) 2 d θ = 9 ∫ 0 tan − 1 3 4 sec 3 θ tan 2 θ + 2 sec 4 θ tan θ + sec 5 θ d θ = 9 ∫ 0 tan − 1 3 4 sec 5 θ − sec 3 θ + 2 sec 4 θ tan θ + sec 5 θ d θ = 9 ∫ 0 tan − 1 3 4 2 sec 5 θ − sec 3 θ + 2 sec 4 θ tan θ d θ = 1 8 ∫ 0 tan − 1 3 4 sec 5 θ d θ − 9 ∫ 0 tan − 1 3 4 sec 3 θ d θ + 1 8 ∫ 0 tan − 1 3 4 sec 4 θ tan θ d θ See: reduction formula = 1 8 ( 4 3 ∫ 0 tan − 1 3 4 sec 3 θ d θ + 4 sec 3 θ tan θ ∣ ∣ ∣ ∣ 0 tan − 1 3 4 ) − 9 ( 2 1 ∫ 0 tan − 1 3 4 sec θ d θ + 2 sec θ tan θ ∣ ∣ ∣ ∣ 0 tan − 1 3 4 ) + 1 8 ∫ 1 3 5 sec 3 θ d sec θ = 1 8 ( 4 3 ( 2 1 ∫ 0 tan − 1 3 4 sec θ d θ + 9 1 0 ) + 8 1 1 2 5 ) − 9 ( 2 1 ∫ 0 tan − 1 3 4 sec θ d θ + 9 1 0 ) + 1 8 ( 3 4 4 5 4 − 4 1 ) = 4 9 ∫ 0 tan − 1 3 4 sec θ d θ + 6 3 = 4 9 ⋅ ln ( tan θ + sec θ ) ∣ ∣ ∣ ∣ 0 tan − 1 3 4 + 6 3 = 4 9 ln 3 + 6 3 ≈ 6 5 . 4 7 2
Reduction Formula: ∫ sec n x d x = n − 1 n − 2 ∫ sec n − 2 x d x + n − 1 sec n − 2 x tan x
In the 5th step . Directly by taking secθ+tanθ=t . We can solve in next two steps very easily
Log in to reply
can u show me how?as i am still ending up with the same integrals
Problem Loading...
Note Loading...
Set Loading...
Putting x = 3 sinh u gives (note that sinh − 1 3 4 = ln 3 ): ∫ 0 4 x 2 + 9 − x x 2 + 9 ( x + x 2 + 9 ) d x = 9 ∫ 0 ln 3 cosh 2 u e 2 u d u = 4 9 ∫ 0 ln 3 ( e 4 u + 2 e 2 u + 1 ) d u = 4 9 [ 4 1 e 4 u + e 2 u + u ] 0 ln 3 = 6 3 + 4 9 ln 3